2014
DOI: 10.1086/676872
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Surgical Site Infections: A Randomized, Open-Label Trial of Nasal Mupirocin Ointment and Nasal Povidone-Iodine Solution

Abstract: Background Treatment of Staphylococcus aureus colonization prior to surgery reduces risk of surgical site infection (SSI). The regimen of nasal mupirocin ointment and topical chlorhexidine gluconate is effective, but cost and patient compliance may be a barrier. Nasal povidone iodine solution may provide an alternative to mupirocin. Methods We conducted an investigator initiated, open label, randomized trial comparing SSI after arthroplasty or spine fusion in patients receiving topical 2% chlorhexidine gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 33 publications
4
131
0
1
Order By: Relevance
“…This is consistent with a recent report of a prospective, open-label, randomized clinical trial where bacterial reduction with 3M SNP resulted in significantly fewer S. aureus SSIs than in mupirocin-treated patients (twice daily for 5 days) undergoing primary or revision arthroplasty or spinal fusion (37).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with a recent report of a prospective, open-label, randomized clinical trial where bacterial reduction with 3M SNP resulted in significantly fewer S. aureus SSIs than in mupirocin-treated patients (twice daily for 5 days) undergoing primary or revision arthroplasty or spinal fusion (37).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Phillips et al conducted a prospective, open-label, randomized clinical study to evaluate 3M SNP as an alternative to intranasal mupirocin because of lack of patient compliance and increasing mupirocin resistance (37). They demonstrated that 3M SNP resulted in significantly fewer S. aureus SSIs than mupirocin.…”
mentioning
confidence: 99%
“…Second, the authors could not perform multivariate analysis due to the small sample size. Third, patients were not followed after discharge to identify late infections (84).…”
Section: Povidone-iodinementioning
confidence: 99%
“…Five RCTs met the inclusion criteria for the review [3337]. Two authors were contacted to clarify questions on study design [33] and the breakout of infections by revision THA/TKA [37].…”
Section: Resultsmentioning
confidence: 99%